Characterisation of a novel proteolytic enzyme localised to goblet cells in rat and man. Issue 6 (June 1984) - Nexø, E; Poulsen, S S; Hansen, S N; Kirkegaard, P; Olsen, P S
Abstract : A proteolytic enzyme, ingobsin, purified from rat duodenal extracts is shown to be localised to intestinal goblet cells of both man and rat. Enzyme positive cells decrease in number from duodenum to colon. The enzyme is a 33 000 Mr protein with an isoelectric point of 5.1. The pH optimum for enzymatic activity is 7.4-8.0. Based on substrate specificity for arg-x, lys-x and to a lesser degree tyr-x, on the effect of diisopropylphosphorofluoride, Trasylol and phenylmethylsulfonylfluoride and on proteolytic activity towards intact proteins, ingobsin is classified as a serine proteinase with endoproteolytic activity.